Writing, paper, book and paper marks in old Turks - Aydın İleri (Türk Kütüphaneciliği)
Mentioned book was prepared by Prof. Şinasi Tekin who is specialized in Turkish ethnology, Turcologist and linguist. Book includes information under the title of role in culturel exchanges of writing and paper, paper-making, kind of papers and printery, manuscript and role of paper mark in its dating.